Spillover effects of immigration policies on children's human capital - Esther Arenas-Arroyo; Bernhard Schmidpeter (Johannes Kepler University of Linz, Department of Economics, 2022)
We study the spillover effects of immigration enforcement policies on children's human capital. Exploiting the temporal and geographic variation in the enactment of immigration enforcement policies, we find that English language skills of US-born children with at least one undocumented parent are negatively affected by the introduction of these policies. Changes in parental investment behavior cause this reduction in children's English skills. Parents are less likely to enroll their children in formal non-mandatory preschool, substituting formal non-mandatory preschool education with parental time at home. Parents also reduce time spent on leisure and socializing, providing children with fewer opportunities to interact and lean from others. Ultimately, these developments reduce children's long-term educational success. Exposure to immigration enforcement during early childhood lowers the likelihood of high school completion. We also find negative, though imprecise, effects on college enrollment.
Keywords: K37; J13; J15; 330; Immigration policies; children’ s human capital; children’ s language skills; parentalinvestment